Efficacy and safety of biosimilar IFX (CT-P13) and adalimumab in patients with active fistulizing perianal Crohn’s disease naďve to anti-TNF therapy: preliminary results from the POLIBD study - Pękala, Anna; Aebisher, David; Pardak, Piotr; Filip, Rafał (European Journal of Clinical and Experimental Medicine, 2019)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction. The development of perianal fistulas are a risk factor in colonic and rectal disease. Perianal CD treatment requires a combination of surgical and therapeutic treatments aimed to prevent septic complications, reduce fistula discharge and ultimately heal fistulas. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Aim. The purpose of the study was to evaluate the efficacy and safety of biosimilar IFX (CT-P13) and adalimumab in active fistulizing perianal Crohn’s disease (CD) in patients from the Subcarpathian Region (South-Eastern Poland). <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and methods. Thirty patients with CD with perianal fistulas naïve to anti-TNF therapy were enrolled (13 females/ 17males) ranging from 18 to 64 years of age. Twenty-one were treated with biosimilar infliximab (CT-P13), nine were treated with adalimumab (ADA). The treated patients had ileal CD (4), ileo-colonic CD (13) or colonic CD (13). All of them received standard immunosuppression with no additional steroid therapy. Response was evaluated at week 16 and 40 after the first CT-P13 dose, and 16 and 40 weeks after the first ADA dose. Remission was defined as the complete closure of all fistulas and partial response as a reduction (≥50%) in the number of draining fistulas. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Results. Treatment outcomes with CT-P13 and ADA were both effective and similar in the percentage of patients with perianal fistula improvement, perianal fistula remission, no effect or observed adverse events. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. In patients with active fistulizing CD, both CT-P13 and ADA were effective and safe, however a slight superiority of CT-P13 was visible.